2010
DOI: 10.1242/dev.052340
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analyses link modulation of sonic hedgehog signaling to continuous variation in facial growth and shape

Abstract: SUMMARYVariation is an intrinsic feature of biological systems, yet developmental biology does not frequently address population-level phenomena. Sonic hedgehog (SHH) signaling activity in the vertebrate forebrain and face is thought to contribute to continuous variation in the morphology of the upper jaw, but despite its potential explanatory power, this idea has never been quantitatively assessed. Here, we test this hypothesis with an experimental design that is explicitly focused on the generation and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
135
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 36 publications
15
135
1
Order By: Relevance
“…Alterations in Shh activity in either the forebrain or facial mesenchyme are known to affect the spatial organization and mitotic activity of midfacial growth zones, resulting in a continuous phenotypic spectrum from cyclopia to hypertelorism. 33,46 Therefore, our data are consistent with the loss of Apaf1 cell-death function causing an increase in Shh signaling that results in the craniofacial development defects we see in the Apaf1 yautja mutants ( Figure 6). …”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Alterations in Shh activity in either the forebrain or facial mesenchyme are known to affect the spatial organization and mitotic activity of midfacial growth zones, resulting in a continuous phenotypic spectrum from cyclopia to hypertelorism. 33,46 Therefore, our data are consistent with the loss of Apaf1 cell-death function causing an increase in Shh signaling that results in the craniofacial development defects we see in the Apaf1 yautja mutants ( Figure 6). …”
Section: Resultssupporting
confidence: 88%
“…[47][48] The current understanding is that the size of the Shh expression region is strictly controlled to coordinate craniofacial development. 33,46 We found increased cell proliferation in the FNP mesenchyme, as would be predicted by increased or persistent Shh signaling from the ventral forebrain signaling center. The broadened, diffuse Shh expression patterns we saw in yautja mutants are concordant with published results in which ectopically expanded Shh activity resulted Figure 5 Craniofacial defects: getting at a mechanism.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, several studies have indicated that the NODAL pathway regulates ventral forebrain patterning through SHH-independent mechanisms (Rohr et al, 2001;Monuki, 2007). SHH might have to reach a threshold concentration to ensure proper forebrain development (Young et al, 2010). The dose-and stage-dependent relationship we observe here is consistent with a threshold effect: slightly reduced NODAL signaling might cause a small downregulation of SHH, which produces a HPE phenotype only when associated with another small decrease in SHH signaling.…”
supporting
confidence: 79%